Educação Física em uma escola do campo: uma experiência com o ensino dos esportes - Silva, Fabiana Francisca de Lima (2020)
School physical education is a discipline that has peculiar characteristics and sport is a teaching content, inseparable from the opportunity to learn to compete. The present study had the objective of developing a Didactic Sequence for the teaching of sports, organizing the modalities by the internal logic and providing for a pedagogical competition in a rural school. During the research, we sought to analyze the students' conceptions and representations about sport and pedagogical competitions, evaluating whether the development of the Didactic Sequence and the proposed competition provided significant learning to students. Sport pedagogy has investigated and expanded the possibilities of understanding the sports phenomenon and has collaborated with current methodologies, which aim to increase the knowledge directed to pedagogical interventions in the teaching and learning processes of sports practices. In order to understand and deepen the central theme of the research, we sought the contribution of several authors who understand competition in the school context as a perspective of integral development, that is, a pedagogical competition and believe in the resignification of school competition as a content to be taught to students. For data collection, participant observations were made, with field diary records, of the pedagogical sequence, as well as of the event; and Focus groups, carried out before and after the sequence of classes and competition. As a main result, major changes were observed in comparison to the organization of events and the teaching of sports in previous years. It was evidenced that the pedagogical process based on a pedagogical competition had an evident impact on individual and collective behavior.